Development of interactive scenario using humanoid robot to assist rehabilitation for children with cerebral palsy / Norjasween Abdul Malik - Abdul Malik, Norjasween (2017)
Human-robot interaction (HRI) has widened their wing to help people with disabilities to improve their quality of life. The use of Socially Assistive Robotics has created a potential approach in Cerebral Palsy (CP) rehabilitation. CP is a common neurological disorder among children that impairs motor function and may involve cognitive function. The objective of the study is to investigate the potential application of humanoid robot NAO as a tool in augmenting rehabilitation therapy for children with CP. Four interactive scenarios were designed to augment rehabilitation therapy for children with CP. Data for Joint Values of the robot NAO for Interactive Scenario 2, 3 and 4 have been recorded. The selected children have been undergone repetitive exposure with the robot for a period of 8 weeks. The experiment indicates that the robot had successfully acted as an adjunct tool in order to motivate the children during the process of robotic rehabilitation. Attention Measurement Checklist has been developed to measure the HRI effectiveness. The children were engaged in the interactions and showed positive responses to the robot. Next is the analysis and comparison of the result of clinical assessment between pre- and post- interaction. The other part of the study is to survey the parents’ perception towards HRI. Overall, this parent strongly agreed with this robotic therapy for their child. With the presence of humanoid robot NAO, there is a good potential to make the therapy more effective since the robotic elements have a potential attraction to the children’s interest.